Auditoría tributaria y su incidencia en la liquidación del impuesto a la renta de la agrícola bananera “El aguacate” cantón Valencia, año 2013 - Calero Lucas, Fiama Beatriz (2015)
This research was conducted at the Agricultural Bananera "El Aguacate" is a family business dedicated to the production and marketing of bananas, it is located in the parish of La Union belongs to the canton Valencia, is registered in the SRI as natural person required to keep accounts and its tax liability payment of Income Tax and Transaction Attachments, so that reason the tax audit is done to avoid future fines and penalties. This audit is based on the provisions of current tax laws. A plan and audit program was conducted. Likewise an array of internal and external media was conducted in order to identify strengths, weaknesses, threats and opportunities in the company, emphasizing the COSO internal control model I with its components and subcomponents, to check the level of tax compliance activities, the study results showed inefficiencies certain findings affecting this area generating tax risks in accounting operations and objectives. Financial Statements where it was observed that the procedures for monitoring the preparation and filing of taxes, just as are not met in all not worth $ 303,206.56 in the box 699 corresponding to the income properly recorded reviewed and $ 29728.01 value of the contribution to IESS thus causing offenses and penalties as established by tax laws and regulations. These results are discussed later be consolidated into a report of tax compliance that was presented to the manager where it is recommended to apply a proper system of internal control that provides efficiency in the procedures established by the company, in addition to monitoring on an ongoing basis that the information matches the declared registered on Form 102 Income tax and apply corrections determinations found in the investigation to avoid future penalties and thereby obtain reasonable information that contributes to the proper filing your taxes.